Outcomes of Total Laparoscopic Hysterectomy Using a 5 mm vs. 10 mm Laparoscope: A Randomized Control Trial. Issue 1 (January 2016) - Acton, Jade N.; Salfinger, Stuart G.; Tan, Jason; Cohen, Paul A.
Abstract : Obstet Gynecol Surv 2016;71(1):17–18 It is standard practice for gynecologic surgeons in Western Australia to use a 10-mm transumbilical laparoscope for minimally invasive hysterectomy. A number of studies have shown that a 5-mm laparoscope is a safe alternative to a 10-mm laparoscope but have not demonstrated a significant decrease in postoperative pain scores.